ATL internals - Rector, Brent; Sells, Chris (Addison Wesley Longman, 1999)
The Active Template Library (ATL) is a set of small, efficient, and flexible classes that facilitate the creation of interoperable COM components. Written for experienced COM and Visual C++ programmers, this book provides in-depth coverage of ATL's inner workings. It offers insight into the rationale behind ATL design, explains its architectural underpinnings, shows how ATL maps to COM, and describes important implementation details.